PENGARUH FAKTOR PRIBADI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPATU VANS PADA KONSUMEN REMAJA DI KOTA KUPANG - Metak, Theresia Kehi; de Rozari, Petrus E; Fanggidae, Ronald P C (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2021)
In terms of purchasing decisions in teenage consumers there are many factors that influence it, namely personal factors such as age, lifestyle, personality, and comfort that can influence a consumer in terms of making purchasing decisions. This study aims to find out partially and simultaneously the influence of age, lifestyle, personality, and comfort on the decision to purchase Vans shoes in Kupang City. This type of research is a survey with a quantitative approach. This research was conducted on teenage consumers in Kupang City with a total sample of 100 respondents who are consumers of adolescents aged 15-24 years in Kupang City. While data collection techniques use observation, questionnaires, and documentation. Variables used include age (X1), lifestyle (X2), personality (X3), comfort (X4) and purchasing decisions (Y). The data analysis used was multiple linear regression (OLS) with a significance level of 5%. The results of this study showed that the variables age (X1) and personality (X3) partially influenced positive and significant impact on the decisions to purchase Vans shoes in Kupang City, while lifestyle variables (X2) and comfort (X4) partially had an insignificant effect on the decisions to purchase Vans shoes in Kupang City. Furthermore, variable age, lifestyle, personality, and comfort simultaneously have a significant influence on the decision to purchase Vans shoes in Kupang City. The amount of independent variable influence is 53.2% and the remaining 46.8% is explained by other variables. Keywords: Age, Lifestyle, Personality, Comfort, and Purchase Decisions.